(untitled) (The Journal of Psychology and Sociology, 2015)
The article presents the main results of a study aimed at identifying and assessing the views of experts teachers of higher educational institutions on competitiveness of university graduates in the labor market. It is quite com mon to consider youth as a vulnerable social category in modern professional labor market, reflecting both regional characteristics and problem areas, and who is a subject to global economic influences. Attitude towards profession als with no work experience and professional life is ambivalent, despite the perception that young people are the most active, energetic and mobile labor force. In this aspect, it is the quality of education, its focus on the highest level, not only knowledge, but also competencies are a crucial factor in the growth of competitiveness of youth in the labor market. The article describes the general characteristics of manifestations of competi tiveness of Kazakhstan’s high school graduate in the labor market in the represen tation of teachers of higher educational institutions of the country. We interpret some of the results of evaluation by experts the degree of university influence on the improvement of the competitiveness of graduates. The role of agents and in stitutions in shaping the competitive qualities of young professionals are analyzed. Practical skills and theoretical knowledge in the professional field identified as the highest priority for the competitiveness of the university graduate. Skills and abilities associated with knowledge superior to significant parameters that char acterize personal potential, in particular, a sense of humor, the ability to have a favorable appearance, common sense, honesty and integrity.